2017
DOI: 10.2147/rru.s140361
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing testicular torsion from torsion of the appendix testis by clinical features and signs in patients with acute scrotum

Abstract: PurposeMany physicians encounter confusion and difficulty in distinguishing testicular torsion (TT) from torsion of the appendix testis (TAT) in patients with acute scrotum because of the overlapping signs and symptoms. The objective of our study was to evaluate the clinical features and signs that can help distinguish TT from TAT.Patients and methodsWe performed a retrospective study of patients with surgically confirmed TT and TAT at our institute from January 1990 to December 2013. Clinical findings, physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 25 publications
4
33
0
Order By: Relevance
“…Overall, 70% had been diagnosed with testicular torsion and the other 30% with torsion of the appendix testis. 2 It was noted that 87.8% of patients with testicular torsion reported a duration of pain of less than 24 hours. The study also reported that more patients with testicular torsion reported or presented with onset of pain during sleep (67.3% vs 33%), testicular swelling (79.6% vs 52.4%) and a high-riding testicle (61.2% vs 33.3%).…”
Section: Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 70% had been diagnosed with testicular torsion and the other 30% with torsion of the appendix testis. 2 It was noted that 87.8% of patients with testicular torsion reported a duration of pain of less than 24 hours. The study also reported that more patients with testicular torsion reported or presented with onset of pain during sleep (67.3% vs 33%), testicular swelling (79.6% vs 52.4%) and a high-riding testicle (61.2% vs 33.3%).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The study also reported that more patients with testicular torsion reported or presented with onset of pain during sleep (67.3% vs 33%), testicular swelling (79.6% vs 52.4%) and a high-riding testicle (61.2% vs 33.3%). 2 Another retrospective study conducted in pediatric patients with a median age of 10 years and presenting with acute scrotum reported that 19 out of 138 patients were diagnosed with testicular torsion. Patients with testicular torsion in this study were on average older age than patients presenting with other causes of acute scrotum.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…While worth knowing, the "blue dot sign" is only present in about 21% (0 to 52%) of all torsed testicular appendages and a false positive "blue dot sign" has been reported in the literature in a patient with testicular torsion [12]. In an effort to improve diagnostic accuracy and avoid needless surgery, precise grey scale and color Doppler ultrasonography have been performed to evaluate the cause of acute scrotum [13]. In young ages, testicular torsion, epididymitis, and torsion of the testicular appendages are the most common etiologies of acute scrotum [8,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Confounding diagnoses include torsion of appendix testis, typically presenting with a more insidious onset and focal tenderness at the upper aspect of the testicle. 3 Epididymo-orchitis has a more insidious onset and may present with fever, dysuria or positive urinalysis. Hydroceles are typically painless and transilluminate.…”
mentioning
confidence: 99%